ANALISIS KESIAPAN PENDIDIK DALAM MEMANFAATKAN MEDIA TIK PADA PROSES PEMBELAJARAN PAI DI ABAD 21 - Hari Ahmad Setyawan; Latifatul Fitriyah; Nurul Alimatul Hargianti (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2022)
In this modern era, the rapid development of technology must be balanced with more understanding and knowledge. It is undeniable that we as young people must participate in this development and strive to be able to compete with others and not to be left behind in information technology matters. In education, teachers or educators have a role in introducing technology using ICT-based learning media. The development of information and technology today has had a very important influence on the learning process and program in learning. this is realized in learning activities such as what has happened recently, namely online learning, blended learning and learning systems carried out remotely. In researchers use qualitative research methods. Qualitative research is a type of research that is based on post-nature positivism with the researcher as the critical tool, as a purposive sampling, data source and snowball. In this method, data collection is carried out using a questionnaire in the form of questions distributed using Google Forms and data analysis.